ADVANCEMENTS IN AUTOMOTIVE BATTERIES: A REVIEW - Akarshan Gulhane; Shilpa Malge; Prof. Eshant G. Rajgure (International Engineering Journal For Research & Development, 2023)
The automotive industry stands at a crossroads, propelled by the urgent need to mitigate climate change and reduce reliance on finite fossil fuel resources. This necessitates a monumental shift towards electric mobility, where electric vehicles (EVs) powered by automotive batteries emerge as the frontrunners in this transformative journey. At the core of this transition lies the automotive battery, a quintessential component that not only propels EVs but also shapes their performance, range, and overall viability. This paper embarks on an extensive exploration of automotive batteries, delving into their evolution, contemporary technologies, and the horizon of future trends and challenges. The transition to electric mobility signifies more than just a change in propulsion systems; it embodies a fundamental shift in the ethos of transportation. By embracing electric vehicles, the automotive industry aims to curtail greenhouse gas emissions, mitigate air pollution, and foster energy independence. At the helm of this revolution, automotive batteries emerge as the linchpin, wielding the power to redefine the dynamics of transportation. This paper endeavors to unravel the intricate tapestry of automotive batteries, tracing their evolutionary trajectory from the humble beginnings of lead-acid technology to the cutting-edge innovations propelling the electric revolution forward. By scrutinizing the past, dissecting the present, and envisioning the future, this study seeks to offer a comprehensive understanding of automotive batteries, thereby contributing to the discourse surrounding the future of transportation.